Electronic Land Certificates as Evidence of Ownership: An Analysis under Indonesian Civil Procedure Law - Noor, Aslan; Khoerunisa, Alsa Mala; Julianti, Frida; Zulkarnain, Muhammad Azka Izzaturrahman; Bahyudin, Mukhamad; Lumbantoruan, Sukmawati; Praidno, Zahra Ardhanie (Jurnal Ilmiah Global Education, 2025)
This study aims to analyze the implementation of electronic land certificates in Indonesia and their role within the civil procedural law framework, particularly in strengthening legal certainty and protection for landowners. The research further seeks to identify challenges associated with electronic certification, such as data security risks and potential disputes, and to explore strategies for enhancing trust and reliability in the electronic certificate system. Employing a normative legal research method, this study relies on statutory and conceptual approaches. Primary legal sources include relevant legislation, notably the Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN) Regulation No. 3 of 2023 on the issuance of electronic certificates, as well as the ITE Law. Secondary and tertiary sources, including scholarly literature and legal dictionaries, are used to provide interpretive depth and contextual analysis. The findings reveal that electronic certificates are legally recognized as valid evidence, bearing equal probative value to physical certificates in civil litigation. Their introduction enhances administrative efficiency, reduces risks of loss, forgery, and corruption, and promotes transparency in land management. Legal protection for certificate holders is provided through consumer rights, personal data protection regulations, and safeguards against cybercrime. However, implementation faces obstacles related to infrastructure readiness, regulatory harmonization, cybersecurity threats, and limited public awareness. In conclusion, the transition toward electronic land certification represents a significant step in digitalizing public administration, reinforcing legal certainty, and fostering efficiency in land registration. Nevertheless, sustained efforts are required to strengthen security protocols, enhance legal frameworks, and promote public trust through socialization and education programs. The contribution of this study lies in offering a comprehensive legal analysis of electronic land certificates as instruments of evidence in civil proceedings, while also providing practical insights for policymakers, legal practitioners, and stakeholders in advancing a more secure and transparent land administration system.